2022
DOI: 10.1039/d1nr07226a
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for interface issues and challenges of neural electrodes

Abstract: Neural electrodes, as a bridge for bidirectional communication between the body and external devices, are crucial means for detecting and controlling nerve activity. The electrodes play a vital role in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 218 publications
(249 reference statements)
0
21
0
Order By: Relevance
“…Hydrogels can generate ion current through dissolving the ions that were adsorbed in the polymer network of the hydrogel into water. Particularly worth mentioning is the porous structure of hydrogels can provide sufficient space for the doping of other conductive materials, thus further improved the electrochemical properties of the networks without sacrificing hydrogels' biological characteristics (Fu et al, 2020; C. Liang et al, 2022). The Young's modulus of hydrogels is very low that can minimize the mismatch of chemical components between the electronic devices and the biological tissue.…”
Section: Materials For Neural Engineering Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels can generate ion current through dissolving the ions that were adsorbed in the polymer network of the hydrogel into water. Particularly worth mentioning is the porous structure of hydrogels can provide sufficient space for the doping of other conductive materials, thus further improved the electrochemical properties of the networks without sacrificing hydrogels' biological characteristics (Fu et al, 2020; C. Liang et al, 2022). The Young's modulus of hydrogels is very low that can minimize the mismatch of chemical components between the electronic devices and the biological tissue.…”
Section: Materials For Neural Engineering Interfacementioning
confidence: 99%
“…Ever since the 1960s, neural electroactive interfaces have been applied to record neural signals and stimulate neural tissue in both experimental animals and humans (Evarts, 1966; Marg & Adams, 1967). With the development of new materials and advanced fabrication technologies, more and more new‐type neural interfaces are developed and the interfaces can play a crucial role in treating many debilitating diseases like paralysis, blindness, deafness, epilepsy, and Parkinson's disease (Fattahi et al, 2014; C. Liang et al, 2022). Deep brain stimulation is a typical example of the neural electroactive interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study reported by Shuang et al demonstrated that Tungsten electrodes with nanoporous features showed reduced signal attenuations indicating enhanced consistency as compared with the smother electrodes [ 137 ]. These studies further suggests that the nanoporous materials have greater applications in bioelectronics space, since they have the potential to exhibit excellent electrochemical properties, biocompatibility, and stability [ 138 ].…”
Section: Biomedical Applications Of Nanoporous Materialsmentioning
confidence: 99%
“…16,17 Ongoing efforts to mitigate this problem should include developing deformable and conformable materials with favorable electrical properties. 3,18,19 Hydrogels have been gaining growing attention as interfaces between biological and engineered systems due to their tissuelike mechanical properties. 5,20,21 They are promising candidates for neural interfaces since they feature a very low Young's modulus (∼kPa) compared to both thermoplastics and elastomers (∼MPa) and gold and platinum (∼GPa).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The acquisition of neural signals from the brain cortex has always been of high relevance in the field of neuroscience. , Moreover, the extension of the electrophysiological recording/stimulation in the brain cortex from days to years may help understand brain processes and neurological diseases and disorders. Compared to electroencephalography (EEG), electrocorticography (ECoG) can improve the spatial specificity, amplitude, and signal-to-noise ratio since the electrodes are placed directly on the cortical surface. , ECoG is beneficial in monitoring epilepsy for presurgical planning and is a therapeutic tool for reducing seizures or neuropathic pain. , In addition, due to its high signal-to-noise ratio and localized cortical signal, ECoG can be used for neuroprosthetic research to provide sensory feedback of external devices in the brain–machine interface. Conventional subdural or epidural electrodes, however, may show immune responses that lead to the fibrous encapsulation of the probe due to a chemomechanical mismatch between the probes and neural tissues. Conventional solid-state interfaces are not specifically designed to fit the complex mechanical properties of tissues and may injure soft tissues. , Most importantly, an inadequate conformability with the brain cortex might lead to inaccurate signal recordings and potential misdiagnosis. , Ongoing efforts to mitigate this problem should include developing deformable and conformable materials with favorable electrical properties. ,, …”
Section: Introductionmentioning
confidence: 99%